The Influence of Brand Image, Price Perception, and Electronic Word of Mouth on Purchase Interest on the Tokopedia E-Commerce Site ( Study on Students in the City of Semarang) - Fidyah Yuli Ernawati; Silvia Hendrayanti; Wachidah Fauziyanti (Sean Institute, 2024)
The purpose of this study is to ascertain and evaluate the impact that pricing perception, electronic word-of-mouth, and brand image have on the inclination to buy on the Tokopedia e-commerce platform (study of students in Semarang City). Students in Semarang were the population under study in this study. Students from different Semarang-based institutions and universities make up this demographic. Since the dependent variable in this study is purchasing interest, the population that will be examined in this research consists of Semarang students who have made purchases online from August to September of 2023 using the e-commerce platform Tokopedia. Anyone who occurs to use the Tokopedia application for transactions involving purchases and sales is included in the sample from this population. The findings of this study indicate that interest in making purchases on the Tokopedia e-commerce platform is significantly, favorably, and strongly influenced by the brand image variable (X1). The brand image that was acquired from Tokopedia is fairly positive, but there are a few indicators that should be taken into account. These include the benefits (benefits) associated with the usefulness of the product and the brand attitude (brand attitude), which is the consumer's attitude regarding their overall assessment of the brand. When taken as a whole, brand image can persuade customers—in this example, Semarang City students—to make purchases. The findings of the research indicate that purchasing choice variables are significantly, strongly, and favorably influenced by the electronic word-of-mouth variable (X2). Electronic word-of-mouth about interest in purchases is fairly strong; nevertheless, there are a few areas that need to be addressed going forward, including the frequency of both positive and negative evaluations, as well as the accuracy and completeness of the information. In general, electronic word of mouth can stimulate buyers—in this example, Semarang City students—to make purchases. The same is true of how people perceive prices.